2018
DOI: 10.1002/bbb.1950
|View full text |Cite
|
Sign up to set email alerts
|

Carbon emission and ethanol markets: evidence from Brazil

Abstract: The production of ethanol has increased globally over the last decade. It is mainly produced from corn and sugarcane, so earlier studies mainly investigated the impact of food prices on ethanol prices. Although biofuels have been brought into the energy markets to reduce the volume of carbon emissions, the links between ethanol and carbon emission markets have not been explored sufficiently in the existing literature. This study aimed to extend the literature in this field by using a GARCH‐jump process to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 19 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…It is to be expected that, due to the sample limitation, variations in correlations will arise between CBIO and Platts ethanol and CBIO and Brazilian ethanol. In the short term, evidence suggests divergence in Brazilian and American ethanol prices, while in the long term, a trend of price convergence becomes apparent (Dutta 2020 ; Hernandez et al 2020 ; Quintino et al 2021b ). Despite the positive correlation between Brazilian ethanol and international oil prices, a large part of the Brazilian ethanol supply is absorbed by domestic market demand, which tends to limit the transmission of international price shocks to domestic prices in the short term.…”
Section: Resultsmentioning
confidence: 99%
“…It is to be expected that, due to the sample limitation, variations in correlations will arise between CBIO and Platts ethanol and CBIO and Brazilian ethanol. In the short term, evidence suggests divergence in Brazilian and American ethanol prices, while in the long term, a trend of price convergence becomes apparent (Dutta 2020 ; Hernandez et al 2020 ; Quintino et al 2021b ). Despite the positive correlation between Brazilian ethanol and international oil prices, a large part of the Brazilian ethanol supply is absorbed by domestic market demand, which tends to limit the transmission of international price shocks to domestic prices in the short term.…”
Section: Resultsmentioning
confidence: 99%
“…The literature has reached different conclusions on whether a significant correlation exists. The empirical results of Kumar et al (2011) and Dutta et al (2018) failed to prove a significant relationship, but other scholars have suggested that a positive correlation between the carbon market and clean energy exists (Dutta & Bouri, 2018; X. Wang et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 98%
“…This tends to favor investments that contribute to mitigating the effects of greenhouse gas emissions (GHG), gradually becoming more evident in the market. Carbon emission prices emerge as a need for pricing this externality, as well as its possible relationship with prices of other renewable energies, such as Brazilian ethanol [20].…”
Section: Literature Reviewmentioning
confidence: 99%